Carob Seeds: Food Waste or Source of Bioactive Compounds? - Debora Santonocito; Giuseppe Granata; Corrada Geraci; Annamaria Panico; Edy Angela Siciliano; Giuseppina Raciti; Carmelo Puglia (MDPI AG, 2020)
(1) Background: For centuries, carob fruit has been used in the food field, while carob seeds have been mainly considered as food waste. Nowadays, there has been considerable attention toward the recovery of the waste plant matrices as possible sources of functional compounds with health properties. Therefore, our goal was to evaluate the health properties of carob seed extracts, and to study the effects of the ripening process on the chemical composition of the extracts. (2) Methods: After the mechanical separation of seeds from carob fruit, an ultrasound-assisted extraction (UAE) was performed to maximize and preserve the quality of bioactive compounds. Seed extracts were characterized by high-performance liquid chromatography (HPLC) and liquid chromatography/mass spectrometry (LC/MS) for the content of bioactive polyphenols, and were finally analyzed by oxygen radical absorbance capacity (ORAC), NO Scavenger (NO) and advanced glyoxidation end products (AGEs) assays, in order to estimate the antioxidant potential of the active compounds. (3) Results: Although both seed extracts of carob unripe (CAR-UR) and ripe (CAR-R) showed an interesting antioxidant activity, CAR-R had greater activity due to the procyanidins content. (4) Conclusions: Based on the obtained results, carob seed extracts could be regarded as interesting source of bioactive antioxidant compounds for a potential application in nutraceutical and food supplement fields.